Fear of COVID-19 and its Differential Effect on Attitudes and Intentions towards Online and Face-to-Face Counseling - Jae Hun Shin; Xyle Ku (Health Psychology Research)
The present study examines the impact of fear of COVID-19 on attitudes and intentions towards online and face-to-face counseling. A total of 526 adults participated in this study. The path analysis results indicated that attitude towards online and face-to-face counseling differentially mediated the relationship between COVID-19 fear and both counseling intentions, even when controlling for other covariates. Specifically, fear of COVID-19 predicted positive attitudes towards online counseling (value of counseling), which in turn, predicted online counseling intention. On the other hand, COVID-19 fear affected negative attitudes towards face-to-face counseling (discomfort with counseling), resulting in a decrease in face-to-face counseling intention.